A feasibility evaluation of oral pressure therapy for the treatment of obstructive sleep apnea. (February 2013) - Farid-Moayer, Mehran; Siegel, Lawrence C.; Black, Jed
Objective: This feasibility study examined the initial-use safety and potential utility of a novel noninvasive oral pressure therapy (OPT) system designed to reduce airway obstruction during sleep. Methods: This was a single-center, proof-of-concept, single-treatment-night study in which subjects with obstructive sleep apnea (OSA) underwent a baseline polysomnography (PSG) study followed by PSG during use of an OPT system. The OPT system is composed of a bedside console, a polymer mouthpiece, and a flexible tube connecting the mouthpiece to the console. The console contains a pump that creates vacuum intended to pull the soft palate anteriorly and stabilize the tongue to reduce obstruction during sleep. Results: Fifty-four men and 17 women, aged 53.2 ± 11.5 years (mean ± SD) had a baseline apnea–hypopnea index (AHI) greater than 5 events per hour. OPT was generally well tolerated with no serious adverse events. OPT significantly decreased AHI from 34.4 ± 28.9 events per hour (mean ± SD) at baseline to 20.7 ± 23.3 ( p < 0.001). Treatment produced an AHI less than 10 in 48% of the subjects. OPT significantly improved oxygen desaturation index ( p < 0.001) and increased the percentage of the night with oxygen saturation of 90% or greater ( p = 0.028). Stage-N1 sleep shifts, total sleep-stage shifts, awakenings and the percentage of sleep time spent in N1 sleep were significantly reduced with treatment. Conclusion: This proof-of-concept study suggests that OPT can produce clinically relevant relief of OSA in certain subjects who are readily identified by PSG during trial use of the noninvasive system. OPT shows promise as a new treatment option for OSA in appropriate patients.